2021
DOI: 10.1002/lary.29594
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chronic Hypoventilation Among Infants With Robin Sequence Using Capillary Blood Gas Sampling

Abstract: Objectives/Hypothesis: To describe the use of capillary blood gas (CBG) sampling to detect and quantify hypoventilation in infants with Robin sequence (RS).Methods: Case series with chart review at two institutions. Infants with RS presenting over a 10-year period were identified using departmental databases. CBG values obtained during infancy or until airway intervention (AI) were reviewed.Results: From 2008 to 2018, 111 infants with RS were identified as having had been assessed and managed from birth or tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…At both institutions, patients in this study underwent continuous pulse oximetry and capillary blood gas (CBG) drawn in the first 24 hours of evaluation and typically 2 days following the initial CGB. 19 Conservative management with positioning was attempted first by placing the patient in a prone position if they had desaturations while supine. Intervention with a nasal trumpet also was attempted.…”
Section: Methodsmentioning
confidence: 99%
“…At both institutions, patients in this study underwent continuous pulse oximetry and capillary blood gas (CBG) drawn in the first 24 hours of evaluation and typically 2 days following the initial CGB. 19 Conservative management with positioning was attempted first by placing the patient in a prone position if they had desaturations while supine. Intervention with a nasal trumpet also was attempted.…”
Section: Methodsmentioning
confidence: 99%
“…Fahradyan et al (2019) reported the use of CBG CO 2 in 73 patients with RS and stated that ROC curves with cutoff value of pCO 2 level of 49.5 is the best among other variables in terms of specificity and sensitivity combination as an “indication” for surgical intervention. Kwan et al (2021) also noted that a PCO 2 cutoff of 55 mmHg (sensitivity = 55.7%; specificity = 91.3%; area under the curve = 0.78) and a HCO 3 cutoff of 30 mEq/L (sensitivity = 56.2%; specificity = 95.0%; area under the curve = 0.80) were most predictive of patients who “required” a surgical airway. Neither of these studies documented how the authors determined surgical airway indications, raising the question of circular reasoning, ie, the factors found by the authors to “predict” the need for surgical airway were, in fact, the very reasons used to determine the “need” for surgery.…”
Section: Discussionmentioning
confidence: 97%